Reading Tudor-Stuart texts through cultural historicism - Tricomi, Albert H., 1942- (University Press of Florida, 1996)
In an assessment of the new historicism as a form of historical knowledge, Albert Tricomi moves beyond it to present what he calls new, cultural historicism. In pursuing this theme, he examines Tudor-Stuart representations of surveillance and the cultural oversight of the sexual body as revealed in Elizabethan-Jacobean drama to bring together two discourses that have not been joined before. Tricomi shows the inadequacy of an older, event-based historical criticism that excludes various forms of cultural knowledge, including metaphor and states of mind as revealed in literary texts. At the same time, he demonstrates a more robust historicism by joining functional cultural analyses to a conception of historical understanding that can recognize both events and processes. Tricomi suggests new and controversial possibilities of what historicized literary studies might be. His study will contribute to the emergence of a more extensive and vigorous cultural historicism. -- Provided by publisher.
Keywords: English literature -- Early modern, 1500-1700 -- History and criticism -- Theory, etc.; Literature and history -- Great Britain -- History -- 16th century.; Literature and history -- Great Britain -- History -- 17th century.; Great Britain -- History -- Tudors, 1485-1603 -- Historiography.; Great Britain -- History -- Stuarts, 1603-1714 -- Historiography.; Historicism.; Littérature et histoire -- Grande-Bretagne -- Histoire -- 16e siècle.; Littérature et histoire -- Grande-Bretagne -- Histoire -- 17e siècle.; Grande-Bretagne -- Histoire -- 1485-1603 (Tudors) -- Historiographie.; Grande-Bretagne -- Histoire -- 1603-1714 (Stuarts) -- Historiographie.; Historicisme.; historicism (theory); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Historicism; Historiography; Literature and history; Great Britain; English Literature.; English.; Languages & Literatures.; 1485-1714; Criticism, interpretation, etc.; History